Development of a semi–empirical reaction kinetic model for PEM fuel cells - Fortuin, Adrian Charles (Department of Chemical Engineering, 2014)
In the drive to more sustainable energy production, polymer electrolyte fuel cells (PEFC) have been at the pinnacle of global research. One of the major drawbacks of PEFCs is therequirement for expensive noble metal catalysts (platinum and ruthenium). Furthermore 75% of the overpotential losses at the cathode are due to the activation of the oxygen reduction reaction (ORR). To reduce the platinum content requirements and understand the cause of the large overpotential of the ORR, a fundamental understanding of the reaction mechanism and the manner in which it proceeds under different operatingconditions is required. Presently, there still remains a large debate in literature around the mechanism followed by the ORR.This study developed a kinetic model from conventional kinetic isotherms and it is proposed that an associative adsorption mechanism occurs at a low overpotential resulting in the dissociation of the hydroperoxyl species determining the rate of the ORR at the cathode of the PEFC. In order to explain the above phenomena a kinetic model was developed, based on the Eley-Rideal mechanism. Furthermore, experiments were conducted at different oxygen partial pressures and low potentials whereby the associative mechanism is believed to dominate. Under these conditions linear sweep voltammograms were recorded. Regression of the derived kinetic model, by using the values for oxygen partial pressure, applied overpotential and kinetic current allowed for the determination of the kinetic constant of a polycrystalline platinum catalyst for ORR.